2023
DOI: 10.1007/s00586-023-07542-6
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS Prize in Bioengineering Science 2023: Age- and sex-related differences in lumbar intervertebral disc degeneration between patients with chronic low back pain and asymptomatic controls

Abstract: Purpose Clinical management of disc degeneration in patients with chronic low back pain (cLBP) is hampered by the challenge of distinguishing pathologic changes relating to pain from physiologic changes related to aging. The goal of this study was to use imaging biomarkers of disc biochemical composition to distinguish degenerative changes associated with cLBP from normal aging. Methods T1ρ MRI data were acquired from 133 prospectively enrolled subjects fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Biomechanics analysis of the human spine has shown that female specimens demonstrate a greater overall range of motion in all planes compared to males, regardless of the severity of degeneration 7,14 ; however, this may be due to many factors including differences in spinal anatomy, vertebral anatomy, or tissue laxity. Meanwhile, T1ρ values for the nucleus pulposus (NP) taken from magnetic resonance images of lumbar discs suggest that males may have higher amounts of proteoglycan content than females 15 . Studying sex‐based differences among humans can be difficult due to cultural and gender biases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanics analysis of the human spine has shown that female specimens demonstrate a greater overall range of motion in all planes compared to males, regardless of the severity of degeneration 7,14 ; however, this may be due to many factors including differences in spinal anatomy, vertebral anatomy, or tissue laxity. Meanwhile, T1ρ values for the nucleus pulposus (NP) taken from magnetic resonance images of lumbar discs suggest that males may have higher amounts of proteoglycan content than females 15 . Studying sex‐based differences among humans can be difficult due to cultural and gender biases.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, T1ρ values for the nucleus pulposus (NP) taken from magnetic resonance images of lumbar discs suggest that males may have higher amounts of proteoglycan content than females. 15 Studying sex‐based differences among humans can be difficult due to cultural and gender biases. Research animals, however, live in a controlled environment, allowing for the study of sexual dimorphism while minimizing societal influences.…”
Section: Introductionmentioning
confidence: 99%